2007
DOI: 10.1002/jmri.20959
|View full text |Cite
|
Sign up to set email alerts
|

Upper cervical spinal cord cross‐sectional area in relapsing remitting multiple sclerosis: Application of a new technique for measuring cross‐sectional area on magnetic resonance images

Abstract: Purpose: To measure accurately the upper cervical cord cross-sectional area (CSA) in patients with relapsing remitting multiple sclerosis (RRMS), and normal control subjects, to address the paradox that longitudinal reduction in CSA has been detected in RRMS while reduction compared to controls has not. We hypothesized that a lack of statistical power and/or measurement sensitivity due to partial volume averaging in previous studies contributed to this paradox. Materials and Methods:Using a technique that corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 32 publications
10
37
1
Order By: Relevance
“…The results of our current study have particular implications for studies of spinal cord disorders that involve an inflammatory response. For example, previous cross-sectional studies have shown that cord volume in MS patients can be increased (with varying levels of statistical significance) when compared with healthy controls, especially in early MS. 3,9 These findings are somewhat unintuitive for a neurodegenerative disease but are hypothesized to reflect the presence of inflammation and associated edema, which can induce a temporary increase in cord volume. Our current results help to bolster that hypothesis by demonstrating that measurable volume changes are associated with fluctuations in water content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our current study have particular implications for studies of spinal cord disorders that involve an inflammatory response. For example, previous cross-sectional studies have shown that cord volume in MS patients can be increased (with varying levels of statistical significance) when compared with healthy controls, especially in early MS. 3,9 These findings are somewhat unintuitive for a neurodegenerative disease but are hypothesized to reflect the presence of inflammation and associated edema, which can induce a temporary increase in cord volume. Our current results help to bolster that hypothesis by demonstrating that measurable volume changes are associated with fluctuations in water content.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] However, there have been contradictory findings in patients with the relapsing remitting form of MS (RRMS), which typically precedes a more progressive form. A number of studies have found that cord CSA is not reduced in RRMS patients 8,9 and could be used to distinguish progressive MS from RRMS patients, 8 whereas others have shown that cord atrophy is detectable in RRMS patients. 10 The inconsistent findings of cord involvement in RRMS may be because of many reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published works on segmentation of the human spinal cord have involved several classes of algorithms, such as contour and edge detection [2], seeded region growing [3] and B-spline active surface [4]. However, previous works generally require high computational effort which can be time-intensive and not suited to an interactive scenario like a CAD.…”
Section: Introductionmentioning
confidence: 99%
“…The segmentation methods in the published papers have been tailored with several classes of algorithms, such as contour and edge detection [5], seeded region growing [6] and B-spline active surface [7], which are not suited to an interactive scenario requirement in CADS.…”
Section: Introductionmentioning
confidence: 99%